DAMPAK PANDEMI TERHADAP UMKM DI DESA UJUNG JAYA KABUPATEN SUMEDANG - Adelse Prima Mulya; Siti Mutia Kosassy; Nelly Suryani; Yurismen Efendi (Jurnal Public Administration, Business and Rural Develoment Planning, 2022)
The COVID-19 pandemic has hit the world, including Indonesia, and has had various impacts, including MSMEs. This study aims to determine the impact of Covid-19 on the UMKM of Ujung Jaya Village at this time. This type of research is descriptive qualitative by using secondary data from research results and literature references regarding data and information related to research. The results of this study show the impact of the Covid-19 pandemic on MSMEs, the challenges of MSMEs during the Covid 19 Pandemic and the MSMEs Strategy in dealing with Covid 19 in Ujung Jaya Village. The impact of the pandemic in Ujung Jaya Village is quite strong, many MSME players have suffered losses due to a decrease in people's purchasing power and a reduction in the production process. It is recommended that to overcome the impact of the pandemic in Ujung Jaya Village, MSME actors can switch to the concept of going digital with the use of social media and other e-commerce to revive their MSME movement